Effect of annealing on humidity sensing properties of Sm-doped SnO2 thin films - R Bakiya Lakshmi; A Vimala Juliet (Journal of Materials Research and Technology, 2019)
Samarium doped tin oxide (Sm-doped SnO2) nanoparticles were sputter deposited on a Silicon substrate to investigate the effect of dopant on humidity sensing properties of tin oxide thin films. Post deposition treatment was done to improve the surface roughness for more reaction sites to be formed. The thickness of thin film was 100 nm and the average grain size of doped samples was found to be 24 nm with a low dopant concentration.SEM and AFM characterizations of annealed samples were done and resistance variations with respect to humidity were experimentally recorded for the samples. The resistance of the Sm-doped thin film was found to reduce from 1.435MΩ to about 0.4MΩ for increasing humidity values of 30–90%RH and gave an appreciable current output in the range 4.34–12.5 μA. The Sm-doped sample exhibited improved sensitivity as compared to pure tin oxide and hence can be employed for real-time humidity measurements. Keywords: Sputtering, Tin oxide, Samarium, Humidity